The Reckoning: The Battle for the International Criminal Court - Yates, Pamela; Onis, Paco de; Kinoy, Peter (Skylight Pictures, 2009)
Verzio FF Submission The International Criminal Court represents the most ambitious attempt ever made to apply the rule of law on a global scale and to protect the most basic human rights. The film follows ICC prosecutor Luis Moreno-Ocampo for three years across four continents as he and his team tirelessly issue arrest warrants for Lord’s Resistance Army leaders in Uganda, prepare to put Congolese warlords on trial, challenge the UN Security Council to bring Sudan's president to justice for the Darfur massacres, and shake up the Colombian justice system. Moreno-Ocampo has a mandate but no police force. At every turn he must put pressure on the international community to muster political clout for the cause. Will the court succeed and will the world ensure that justice prevails?